2021
DOI: 10.3390/pr9020272
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Tribological Properties of Graphene Lubricant Additives for Low-Sulfur Fuel by Dielectric Barrier Discharge Plasma-Assisted Ball Milling

Abstract: Poor lubrication performance of low-sulfur fuel leads to increased wear of diesel engine components. In order to improve the lubrication properties of low-sulfur fuel, we successfully prepared graphene lubricant additives by dielectric barrier discharge plasma-assisted ball milling. The tribological properties of graphene lubricant additives in two types of 0# diesel oils with different sulfur content were evaluated by high-frequency reciprocating rig (HFRR). The results indicated that the expanded graphite wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Our findings suggest that 0.05 wt% as the optimal graphene nanoparticle concentration to be dispersed in base POE oil. This finding is, to some extent, in line with the findings of [40], which revealed that an addition of 0.03% graphene nanoparticles in diesel oil reduces COF by 20%. Similarly, another study [41,42] concluded that 0.05 wt% graphene nanoparticles significantly results in the reduction of COF.…”
Section: Friction Response Of the Samplessupporting
confidence: 91%
“…Our findings suggest that 0.05 wt% as the optimal graphene nanoparticle concentration to be dispersed in base POE oil. This finding is, to some extent, in line with the findings of [40], which revealed that an addition of 0.03% graphene nanoparticles in diesel oil reduces COF by 20%. Similarly, another study [41,42] concluded that 0.05 wt% graphene nanoparticles significantly results in the reduction of COF.…”
Section: Friction Response Of the Samplessupporting
confidence: 91%
“…Frequently used nanoscale lubricant additives are metals, metal oxides, metal sulfides, metal borates, polymers, and carbon-based nanomaterials [18][19][20]. However, nanoscale carbon materials have become increasingly popular in the lubricant additive community due to their ecologically approachable nature, exceptional self-lubricating behavior, good chemical and high thermal stability and outstanding mechanical properties with respect to bulk carbon materials [21][22][23]. As shown in Figure 1, the most commonly used carbon-based lubricant additives are fullerene, graphene, nano-graphite, carbon nanotubes, and other bulk carbon materials.…”
Section: Introductionmentioning
confidence: 99%